Understanding pharmaceutical wet granulation in a twin screw extruder - Li, Huiying (My University, 2014)
Granulation is an important process for industries ranging from plastics to food and pharmaceutics. In the last decades, the twin-screw extruder has been more and more studied as a continuous method for granulation. But there are many questions remaining to be answered such as the functions of kneading block and the granulation behavior in this zone, the influence of the wetting method, and also the influence of the active pharmaceutical ingredient (API) properties on the granulation process. Therefore, in this project, a series of experiments were performed based on a new technique to the granulation field named ‘screw pullout’ for understanding the granulation process within the twin-screw extruder. In order to understand the specific function of an important screw element known as a kneading block, the physical particle motion reflecting progress of granulation was monitored along the screw. Different feed rate and formulations were studied; the residence time and pressure in kneading block were measured; and the granules along the screw were characterized for their porosity and size distribution. It was found that granule consolidation and breakup within the kneading block allowed the production of granules with consistent properties and excellent mechanical strength. However, the changes produced by a kneading block are dependent upon the formulation. For example, the kneading block demonstrates no observable function with formulations containing a significant content of microcrystalline cellulose. The most notable benefit of the kneading block to all tested materials appeared to be distribution of the interstitial binding liquid rather than to compact the powders. A new wetting method using a foam binder has been studied intensively in this work to assess its influence on the granulation process. A series of studies have been performed to compare the granule development along the screws as powder formulation and screw design were varied to test for the differences induced by the two wetting methods (foam delivery or liquid injection). The evolution of the granules along the screw was characterized by analyzing the particles size distribution, porosity, and fracture strength. It was found that the wetting method had minor impact on the particle size distribution due to the strong mechanical dispersion inherent to the extruder. The major finding for the pharmaceutical industry was that the foam method reduces the required amount of liquid to granulate, thereby dropping drying time after the process. The foamed binder was also found to be preferred when the formulation contains powder components with poor spreading properties. Finally, the influence of an API’s physical properties on granulation was studied by comparing formulations with varying API hydrophobicity. It was found that the API and binder distribution was not affected by the hydrophilicity of API, while the particle size distribution, porosity and fracture strength were strongly dependent on the properties of the API.
Keywords: wet granulation; twin screw extruder; foam delivery; extrusion